Nilai Pembuktian Saksi Perempuan Dalam Hukum Islam - Wahyudi, Muhamad Isna (Musawa Jurnal Studi Gender dan Islam, 2009)
Female witness in Islamic Law as understood by the Islamic jurists is a half of that of male. The Quran also states it distinctly in 2:282. Of course, it seems to be discriminative against women. The question now, does that provision prevail temporally or universally? What is the historical situation proceeding the provision? According to the author, the provision that female witness is a half of that of male is temporal and not universal. It needs two women to bear witness to be equal with the male witness due to the lack of women experience in public matters. So if one is hesitate to bear witness, another is able to remind her. It is important to note that at the time of revelation, the roles of women in Arabia were generally restricted in domestic sector. Therefore, at this time when the women have equal chance with the men to reach higher study, work in public sector and be the president of a nation, it is supposed to treat female witness equal with that of male.